The use of the Game Theory Context in the strategic political marketing design. The case of the USA elections. - Markaki, Evangelia; Chadjipadelis, Theodore (International Conference on Business and Economics - Hellenic Open University, 2023)
This study presents a conceptual framework approach that can provide useful information about the political strategy via the rational decision-making process, as well as create an efficient tool for political marketing campaigns. Game theory combines the models of conflict and cooperation for people whose decision-making is considered rational. How can this be implemented in voting behavior, influencing a wide range of issues, relations and behaviors? We consider the political competition as a strategic game, where we have to identify the opposing players, the purpose of the game and its rules. Game theory helps us understand the decision-making process towards strategic issues during political competition. The modeling of the voting behavior can explain the way people form theirs in the challenging environment of the political competition. In the present study we will investigate the way game theory can be involved in American elections, trying at the same time to depict behaviors and political marketing strategies. Using the game theory and the political marketing approach, our study examines the different strategies that politicians used during the last American election of 2016, explaining how their strategy influences the result of the elections. We focus mostly on financial, social and environmental issues, but also on issues about security, immigration and international relations. We measure the intensity of the candidates’ focus on these issues and we present two game theory matrixes as examples base on this innovative concept. EL Classifications: G34, G14, M41. Key words: game theory, political marketing, strategy, decision making